2015
DOI: 10.1086/678408
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom Patterns of Genetic Admixture Expose the Complex Historical Hybrid Origin of Unisexual Leaf Beetle Species in the GenusCalligrapha

Abstract: Many unisexual animal lineages supposedly arose from hybridization. However, support for their putative hybrid origins mostly comes from indirect methodologies, which are rarely confirmatory. Here we provide compelling data indicating that tetraploid unisexual Calligrapha are true genetic mosaics obtained via analysis of mitochondrial DNA (mtDNA) and allelic variation and coalescence times for three single-copy nuclear genes (CPS, HARS, and Wg) in five of six unisexual Calligrapha and a representative sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 93 publications
3
37
0
Order By: Relevance
“…In the case of Wg data, ambiguous positions of heterozygotes were resolved in most cases by reference to known alleles in the population as observed in homozygotic individuals in the alignment or, in a second round of inference, considering the new alleles deduced in the previous step. Moreover, relevant in the case of unisexual species of known hybrid origin, these data were aligned and compared with the homologous sequences of putative parental Calligrapha species from Montelongo and Gómez‐Zurita (). Information on sample diversity, including segregating sites, haplotype and nucleotide diversity, and theta, as a measure of divergence, as well as measures of heterozygosity in the case of Wg , were obtained using DnaSP 5.10.1 (Librado & Rozas, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Wg data, ambiguous positions of heterozygotes were resolved in most cases by reference to known alleles in the population as observed in homozygotic individuals in the alignment or, in a second round of inference, considering the new alleles deduced in the previous step. Moreover, relevant in the case of unisexual species of known hybrid origin, these data were aligned and compared with the homologous sequences of putative parental Calligrapha species from Montelongo and Gómez‐Zurita (). Information on sample diversity, including segregating sites, haplotype and nucleotide diversity, and theta, as a measure of divergence, as well as measures of heterozygosity in the case of Wg , were obtained using DnaSP 5.10.1 (Librado & Rozas, ).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the analysis of allelic diversity of three single‐copy nuclear genes in five of the six unisexual Calligrapha species and a representative sample of bisexual species allowed validating this hypothesis. Indeed, individuals of unisexual species proved to be genetic mosaics sharing alleles with two and up to three bisexual species, extant representatives of the lineages involved in independent historical interspecific hybridization events (Montelongo & Gómez‐Zurita, ). Interestingly, this study also revealed some unexpected and intriguing findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disruptions will usually cause aneuploidy, abortive development, and sterility. Both successful lab experiments and careful genomic analyses have shown that interspecific hybridization followed by back-crossing events can indeed result in parthenogenetic reproduction with restoration of ploidy that retains heterozygosity (e.g., Choleva et al, 2012;Drosopoulos, 1978;Lunt et al, 2014;Lutes, Baumann, Neaves, & Baumann, 2011;Montelongo & Gómez-Zurita, 2015;Schultz, 1973;White, Contreras, Cheney & Webb, 1977;Xu et al, 2013Xu et al, , 2015. It is thought that a rare balance between similarity and dissimilarity is necessary (the balance hypothesis, Janko et al, 2018;Moritz et al, 1989;Vrijenhoek, 1989).…”
Section: Hybridization and Endosymbiont Infections Cause Alterationmentioning
confidence: 99%
“…Hence it is vital that there should not be too much dissimilarity. Importantly single interspecific hybridization events are apparently not sufficient to initiate parthenogenesis and complex hybridization patterns appear to be usually necessary (Janko et al, 2018;Lunt et al, 2014, Montelongo & Gómez-Zurita, 2015Moritz et al, 1989;Xu et al, 2015). Both successful lab experiments and careful genomic analyses have shown that interspecific hybridization followed by back-crossing events can indeed result in parthenogenetic reproduction with restoration of ploidy that retains heterozygosity (e.g., Choleva et al, 2012;Drosopoulos, 1978;Lunt et al, 2014;Lutes, Baumann, Neaves, & Baumann, 2011;Montelongo & Gómez-Zurita, 2015;Schultz, 1973;White, Contreras, Cheney & Webb, 1977;Xu et al, 2013Xu et al, , 2015.…”
Section: Hybridization and Endosymbiont Infections Cause Alterationmentioning
confidence: 99%